Analisis Strategi Manajemen Keuangan Internasional dalam Aktivitas Ekspor-Impor pada Perusahaan di Indonesia - Desvanni Habayahan; Agnes Santana Manik; Elsi Natalia Saragih; Marselina Simarangkir; Meijin Saragih; Enzel Hikma Sari Saragih; Chris Damai Yanti Roberkati Pinem; Raya Panjaitan (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
Based on the results of the analysis that has been carried out, it can be concluded that international financial management has a very important role in supporting the company's export-import activities in Indonesia. Companies involved in international trade face a variety of risks, especially exchange rate risks, economic risks, and political risks that can affect a company's financial performance. Therefore, an effective international financial management strategy is needed to manage these various risks so that business activities can run optimally. Strategies that are commonly applied by companies include hedging (hedging), business diversification, currency diversification, cash flow management, and proper capital allocation. The implementation of this strategy has been proven to be able to reduce the impact of exchange rate fluctuations, maintain cash flow stability, increase profitability, and strengthen the company's competitiveness in the international market. In addition, international financial management strategies also contribute to the sustainability of export-import activities by helping companies adapt to changing global economic conditions and take advantage of opportunities available in international markets. Overall, the company's success in implementing an international financial management strategy shows that risk management and proper financial decision-making are important factors in achieving optimal financial performance and sustainable business growth. Therefore, companies need to continue to improve their ability to manage international financial aspects in order to face increasingly complex global challenges and maintain their position in international competition.